2020
DOI: 10.1021/acschembio.9b00894
|View full text |Cite
|
Sign up to set email alerts
|

Selectively Disrupting m6A-Dependent Protein–RNA Interactions with Fragments

Abstract: We report a crystallographic analysis of small-molecule ligands of the human YTHDC1 domain that recognizes N6methylated adenine (m 6 A) in RNA. The 30 binders are fragments (molecular weight < 300 g mol −1 ) that represent 10 different chemotypes identified by virtual screening. Despite the structural disorder of the binding site loop (residues 429−439), most of the 30 fragments emulate the two main interactions of the −NHCH 3 group of m 6 A. These interactions are the hydrogen bond to the backbone carbonyl of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…Based on results from initial optimization we instead performed DMSO-free soaking, in which preselected fragments dissolved in DMSO were deposited onto a crystallization plate with the Echo device, air-dried to remove the solvent and redissolved in the crystallization buffer. Subsequently, 70 YTHDC1 domain crystals were manually transferred to crystallization drops for soaking and harvested (both steps were assisted by the Crystal Shifter), resulting in 30 fragment-bound structures (Bedi et al, 2020). The dedicated Redissolve tab was created in the FFCS GUI on demand for this particular project, enabling the tracking of a DMSO-free soaking experiment in the FFCS DB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on results from initial optimization we instead performed DMSO-free soaking, in which preselected fragments dissolved in DMSO were deposited onto a crystallization plate with the Echo device, air-dried to remove the solvent and redissolved in the crystallization buffer. Subsequently, 70 YTHDC1 domain crystals were manually transferred to crystallization drops for soaking and harvested (both steps were assisted by the Crystal Shifter), resulting in 30 fragment-bound structures (Bedi et al, 2020). The dedicated Redissolve tab was created in the FFCS GUI on demand for this particular project, enabling the tracking of a DMSO-free soaking experiment in the FFCS DB.…”
Section: Discussionmentioning
confidence: 99%
“…After soaking has been completed, the Echo experiment report is sent to the FFCS DB, the Soaking tab timer is stopped, and the soaking status displayed in the FFCS GUI is updated accordingly. The Redissolve tab is an optional step of the FFCS pipeline which was created on demand for a challenging project that required DMSO-free soaking (Bedi et al, 2020).…”
Section: Ffcs Database and Ffcs Guimentioning
confidence: 99%
“…All of these regulatory functions are achieved through its binding to m 6 A-modified RNA and therefore it is necessary to fully understand its molecular recognition mechanism. YTHDC1 is the first human reader protein whose structure was successfully determined and was recently validated as a target of small-molecule inhibitors . These pioneer studies make YTHDC1 an ideal model system for studying the binding mechanisms of reader proteins and their binders.…”
Section: Introductionmentioning
confidence: 99%
“… 109 Bedi et al performed computational screening of fragments and found thirty m 6 A mimics with the potential to bind to reader proteins. 110 There are also few selective modulators for another m 6 A demethylase, ALKBH5. For example, Li et al identified the ALKBH5 inhibitor ALK-04 (the structure remains unreleased) through in silico screening, which significantly enhances the efficacy of anti-PD-1 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, STM2457, a potent and selective METT3 inhibitor has been developed and showed pharmacological effects on AML in mice model 109. Recently, Bedi et al performed computational screening of fragments and found thirty m6 A mimics with the potential to bind to reader proteins 110. There are also few selective modulators for another m6 A demethylase, ALKBH5.…”
mentioning
confidence: 99%